Highly precise plasmonic and colorimetric sensor based on enzymatic etching of nanospheres for the detection of blood and urinary glucose. Issue 19 (29th January 2015) - Jang, Hongje; Min, Dal-Hee
Abstract : A highly precise glucose sensor was developed based on plasmon peak shift induced by the glucose oxidase mediated etching of Au–Ag nanoparticles. The platform enabled quantitative glucose detection in human blood and urine samples. Abstract : A highly precise glucose sensor was developed based on plasmon peak shift induced by glucose oxidase mediated etching of Au–Ag nanoparticles. The present platform enabled quantitative glucose detection in human blood and urine samples owing to its excellent colloidal stability and little interference from UV-vis absorption of biological samples.